(untitled) (Eurasian Journal of Philology Science and Education, 2015)
This article is devoted to the place of the pamphlet in the English writer’s creative activity. Here the main peculiarities of the existing social problems are revealed by this genre. It is commonly known that the English literary conception from the end of the XVII c. up to the beginning of the XVIII c. appealed to the potential opportunities of the given genre.